At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To evaluate the function [tex]\( h(x) \)[/tex] at the given points, let's analyze the piecewise defined function and the appropriate intervals for each given value.
The function is defined as follows:
[tex]\[ h(x)=\left\{\begin{array}{ll} -x^2-6 x-9, & x<-2 \\ \left(\frac{1}{3}\right)^x-4, & -2 \leq x \leq 2 \\ \frac{1}{2} x-4, & x>2 \end{array}\right. \][/tex]
1. Evaluating [tex]\( h(-3) \)[/tex]:
- Since [tex]\(-3 < -2\)[/tex], we use the first piece of the function:
[tex]\[ h(x) = -x^2 - 6x - 9 \][/tex]
Substituting [tex]\( x = -3 \)[/tex]:
[tex]\[ h(-3) = -(-3)^2 - 6(-3) - 9 \][/tex]
Simplifying:
[tex]\[ = -9 + 18 - 9 = 0 \][/tex]
Therefore,
[tex]\[ h(-3) = 0 \][/tex]
2. Evaluating [tex]\( h(-2) \)[/tex]:
- Since [tex]\(-2 \leq -2 \leq 2\)[/tex], we use the second piece of the function:
[tex]\[ h(x) = \left(\frac{1}{3}\right)^x - 4 \][/tex]
Substituting [tex]\( x = -2 \)[/tex]:
[tex]\[ h(-2) = \left(\frac{1}{3}\right)^{-2} - 4 \][/tex]
Simplifying:
[tex]\[ = 3^2 - 4 = 9 - 4 = 5 \][/tex]
Therefore,
[tex]\[ h(-2) = 5 \][/tex]
3. Evaluating [tex]\( h(4) \)[/tex]:
- Since [tex]\(4 > 2\)[/tex], we use the third piece of the function:
[tex]\[ h(x) = \frac{1}{2}x - 4 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ h(4) = \frac{1}{2}(4) - 4 \][/tex]
Simplifying:
[tex]\[ = 2 - 4 = -2 \][/tex]
Therefore,
[tex]\[ h(4) = -2 \][/tex]
Summarizing the results:
[tex]\( \begin{array}{l} h(-3)= 0 \\ h(-2)= 5 \\ h(4)= -2 \end{array} \)[/tex]
The function is defined as follows:
[tex]\[ h(x)=\left\{\begin{array}{ll} -x^2-6 x-9, & x<-2 \\ \left(\frac{1}{3}\right)^x-4, & -2 \leq x \leq 2 \\ \frac{1}{2} x-4, & x>2 \end{array}\right. \][/tex]
1. Evaluating [tex]\( h(-3) \)[/tex]:
- Since [tex]\(-3 < -2\)[/tex], we use the first piece of the function:
[tex]\[ h(x) = -x^2 - 6x - 9 \][/tex]
Substituting [tex]\( x = -3 \)[/tex]:
[tex]\[ h(-3) = -(-3)^2 - 6(-3) - 9 \][/tex]
Simplifying:
[tex]\[ = -9 + 18 - 9 = 0 \][/tex]
Therefore,
[tex]\[ h(-3) = 0 \][/tex]
2. Evaluating [tex]\( h(-2) \)[/tex]:
- Since [tex]\(-2 \leq -2 \leq 2\)[/tex], we use the second piece of the function:
[tex]\[ h(x) = \left(\frac{1}{3}\right)^x - 4 \][/tex]
Substituting [tex]\( x = -2 \)[/tex]:
[tex]\[ h(-2) = \left(\frac{1}{3}\right)^{-2} - 4 \][/tex]
Simplifying:
[tex]\[ = 3^2 - 4 = 9 - 4 = 5 \][/tex]
Therefore,
[tex]\[ h(-2) = 5 \][/tex]
3. Evaluating [tex]\( h(4) \)[/tex]:
- Since [tex]\(4 > 2\)[/tex], we use the third piece of the function:
[tex]\[ h(x) = \frac{1}{2}x - 4 \][/tex]
Substituting [tex]\( x = 4 \)[/tex]:
[tex]\[ h(4) = \frac{1}{2}(4) - 4 \][/tex]
Simplifying:
[tex]\[ = 2 - 4 = -2 \][/tex]
Therefore,
[tex]\[ h(4) = -2 \][/tex]
Summarizing the results:
[tex]\( \begin{array}{l} h(-3)= 0 \\ h(-2)= 5 \\ h(4)= -2 \end{array} \)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.